New optical Heisenberg model with timelike optical de Sitter flux density - Körpınar, Talat; Körpınar, Zeliha; Asıl, Vedat (Elsevier GmbH, 2022)
In this manuscript, we construct new model for de Sitter magnetic Lorentz flux for timelike magnetic T? fiber by de Sitter frame in S12. Then, we present new optical illustrations of timelike magnetic T? fiber by using polarized wave beam fields. Thus, we determine spherical geometric flux surface by spherical flux density. Also, we present new construction for timelike magnetic T? fiber by Heisenberg Sitter ferromagnetic model. Finally, we demonstrate some illustrations of the geometric optical phases in physical optics. © 2022 Elsevier GmbH
Keywords: Ferromagnetic Heisenberg model; Geometric optical phase; Optical frame; Spherical flux; Ferromagnetism; Physical optics; Spheres; Ferromagnetic heisenberg model; Ferromagnetics; Flux densities; Geometric optical phase; Heisenberg models; Lorentz; Optical frames; Optical phasis; Optical-; Spherical flux; Ferromagnetic materials